Duties and decision-making guidelines for Shari'ah committee: an overview of AAOIFI - Amanullah, Muhammad; Mhd Zain, Muhammad Nabil Fikri (IIUM Press, International Islamic University Malaysia, 2018)
The Sharī‘ah ‘Committee is a board which is independent in directing, reviewing and supervising an Islamic Financial Institution (IFI). It consists of those who are specialised in Fiqh Mu‛āmalāt or those who know it with expertise in other fields. In conjunction with IFIs emergence, the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) was established and has issued numerous standards on accounting, auditing and also governance for IFIs. The researchers intend to review the duties and decision-making guidelines of the Sharī‘ah Committee prescribed by the AAOIFI in 2010. The review undergoes a thorough search and critical analysis of any related content about the topic throughout the whole standard. Some important results are: AAOIFI mentions directly the duties of the Sharī‘ah Committee along with the definition of this Sharī‘ah Committee. These duties are directing, reviewing and supervising. On the other hand, decision-making guidelines are indicated indirectly and they are scattered throughout the AAOIFI governance standards.